Development Of Control Algorithm For Spot Cooling System - Andy, Tan Wei Keat (Universiti Sains Malaysia, 2017)
Air conditioner has become the most common electrical appliance in every household. In recent years, the challenge to reduce the energy usage of air conditioner has become a hot topic among researchers. This project’s aim is to develop a Control Algorithm for Spot Cooling system. The system helps to detect and track a non-human decoy. The decoy is designed to be wearable by the user so the air conditioner will blow the air towards the user. The Spot Cooling algorithm is implemented on a Raspberry Pi 3 using Model-Based Design with Matlab. A NoIR camera is used to capture infrared images and the visible light is filtered using a floppy disc film. The non-human decoy which is made up of infrared light emitting diode (IR LED) is detected from the captured image using colour thresholding and template matching techniques. The movement of the decoy is tracked using a Kalman filter. The system was successfully implemented. The detection result was verified using a graphical user interface (GUI) software running on a computer. The experimental results showed that the system can achieve more than 98% of correct detection rate for both day and night conditions.